Reduction of broadcast storm in urban VANETs using network science - Singh, Jagtar; Singla, Sanjay; Jangra, Surender (International Journal of Engineering and Technology, 2018)
VANETs is very interesting research area. Development of an efficient routing protocol in urban VANETs is a very challenging task that can support communication between vehicles with minimum overhead and maximum reachability. The main overhead in urban network is redundant reception of safety or warning messages. Sometimes we call this broadcast storm. In urban VANETs most of message dissemination protocols use broadcast approach to send messages. Broadcast storm is a major problem in high vehicle density area mainly at cross points. In this paper we reduce broadcast storm or communication overhead by using some techniques developed with help of study of network science. In this paper we study various network parameters of VANETs like node degree distribution, clustering coefficient, average shortest path length, network reachability, mobility pattern, road topology, penetration rate and network overhead. We then show how this information can be used to reduce communication overhead in urban vehicular broadcasting protocol (UVCAST) with no major reduction in performance of existing protocol.Â